GRAMATIKAL DALAM TEKS DESKRIPSI PADA SISWA KELAS VIII SMPN 17 PESAWARAN - Surdayati, Surdayati; Supriyono, Supriyono (LPPM STKIP PGRI Bandar Lampung, 2017)
The aims of this research are to describe the references, substitutions, ellipsis, and conjunctions as the instruments of grammatical cohesion between sentences that is used in description text at the students of eighth class of SMP Negeri 17 Pesawaran. This research used qualitative descriptive method. The data was analyzed by used content analysis technique. The data in this research is description text at the students of eighth class of SMP Negeri 17 Pesawaran. To collect the data the writer giving the task to the students of eighth class of SMP Negeri 17 Pesawaran. The data’s sources in this research are the instruments of grammatical cohesion between sentences which are contained in description text at the students of eighth class of SMP Negeri 17 Pesawaran. The result of analysis has found using of the instruments grammatical cohesion in descriptive text at the students of eight class of SMP Negeri 17 Pesawaran that are: (a) 11 types of references a number of 102 usages; (b) 5 types of substitution a number of 33 usages; (c) 3 types ellipsis a number of 15 usages; and (d) 12 types of conjunctions a number of 75 usages.